The Effects of Government Debt on Private Investment in Bulgaria - Nikolova, Velichka (Research Papers, 2021)
The main objective of this study is to establish whether there is a relationship between government debt and private investment in Bulgaria, as well as to identify the impact of debt on investment in the long and short-run period. The cointegration analysis and a model with vector error correction are applied in the research. Empirical findings of the study show that the crowding-out hypothesis in Bulgaria cannot be confirmed.